2014
DOI: 10.7755/fb.112.2-3.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluctuations in sea-surface temperature on the occurrence of small cetaceans off Southern California

Abstract: Abstract-The link between ocean temperature and spatial and temporal distribution patterns of 8 species of small cetaceans off Southern California was examined during the period 1979-2009. Averages and anomalies of sea-surface temperatures (SSTs) were used as proxies for SST fluctuations on 3 temporal scales: seasonal, El Niño-Southern Oscillations (ENSO), and Pacific Decadal Oscillations (PDO). The hypothesis that cetacean species assemblages and habitat associations in southern California waters co-vary with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In recent years, interest has increased in the development of predictive models to forecast near realtime marine mammal distribution as a way to inform, mitigate, and decrease the effect of potentially harmful human activities in the marine environment Forney et al, 2012;Thompson et al, 2012;Henderson et al, 2014). Although our data set spans a 5-year period that ends in 2008, visual and acoustic data on detections of marine mammals continue to be collected with corresponding oceanographic data, both physical and biological, during CalCOFI cruises.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, interest has increased in the development of predictive models to forecast near realtime marine mammal distribution as a way to inform, mitigate, and decrease the effect of potentially harmful human activities in the marine environment Forney et al, 2012;Thompson et al, 2012;Henderson et al, 2014). Although our data set spans a 5-year period that ends in 2008, visual and acoustic data on detections of marine mammals continue to be collected with corresponding oceanographic data, both physical and biological, during CalCOFI cruises.…”
Section: Discussionmentioning
confidence: 99%
“…Dall's porpoise are probably opportunistic foragers, but feed primarily on small schooling fishes, squids and lanternfish (Jefferson, ). Previous studies have found evidence for interannual and seasonal shifts in distribution both north–south and inshore/offshore following the distribution of cool surface waters (e.g., Becker et al., ; Forney & Barlow, ; Henderson et al., ; Tynan et al., ), although the scale of individual movement patterns is not well known (Jefferson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall study area abundance estimates are similar to those derived previously using line-transect analyses (Campbell et al, 2015), but the habitat models provide fine-scale detail in spatial density patterns that are more useful for conservation and management applications. Given the increased use of SDMs to help evaluate and reduce potential risks to cetaceans (e.g., Redfern et al, 2013; U.S. Department of the Navy, 2015), and the documented high degree of seasonal variability in the distribution of cetaceans in the study area (Dohl et al, 1986;Green et al, 1992Green et al, , 1993Forney and Barlow, 1998;Becker et al, 2014;Douglas et al, 2014;Henderson et al, 2014;Campbell et al, 2015), it is critical to develop seasonally-explicit SDMs. Campbell et al (2015) were able to provide separate linetransect abundance estimates for winter and spring seasons; however, in our study sighting data were not sufficient to develop separate habitat models for the two cool seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Such models are particularly important in the marine environment because variability in ocean conditions can result in changes in species distribution. This is especially true in the California Current Ecosystem, where high interannual and seasonal variability in oceanic conditions result in marked shifts in cetacean distribution (Dohl et al, 1978;Forney and Barlow, 1998;Forney, 2000;Becker et al, 2012Becker et al, , 2014Douglas et al, 2014;Henderson et al, 2014;Campbell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation